2022
DOI: 10.1007/s13258-022-01304-2
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing reveals lncRNA-mediated non-mendelian inheritance of feather growth change in chickens

Abstract: Background Long non-coding RNAs (lncRNAs) play an essential role in biological processes. However, the expression patterns of lncRNAs that regulate the non-Mendelian inheritance feather phenotypes remain unknown. Objective This study aimed to compare the expression profiles of lncRNAs in the follicles of the late-feathering cocks (LC) and late-feathering hens (LH) that followed genetic rules and the early-feathering hen (EH) and early-feathering cock (EC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Some signaling pathways and genes were commonly found in previous investigations of birds, such as the TYR gene in chicken [52], the crested ibis [53], and ducks [54]. The melanogenesis pathway found in PSGs of the Temminck's tragopan was also been identi ed in other birds [32,37,38,[55][56][57], such as the chicken based on transcriptome [57] and genomic SNP data [32]. The WNT10A gene was identi ed in melanogenesis pathway in PSGs of the Temminck's tragopan, and a previous study showed that miR-193b might participate in the adjustment of coat color in the skin tissue of Cashmere goats by targeting WNT10A and GNAI2 [58].…”
Section: Plumage Color and Feather Developmentmentioning
confidence: 99%
“…Some signaling pathways and genes were commonly found in previous investigations of birds, such as the TYR gene in chicken [52], the crested ibis [53], and ducks [54]. The melanogenesis pathway found in PSGs of the Temminck's tragopan was also been identi ed in other birds [32,37,38,[55][56][57], such as the chicken based on transcriptome [57] and genomic SNP data [32]. The WNT10A gene was identi ed in melanogenesis pathway in PSGs of the Temminck's tragopan, and a previous study showed that miR-193b might participate in the adjustment of coat color in the skin tissue of Cashmere goats by targeting WNT10A and GNAI2 [58].…”
Section: Plumage Color and Feather Developmentmentioning
confidence: 99%